Antecedentes da aceitação e adoção da auditoria contínua pelos auditores internos - Nascimento, Alexandre Moysés Vargas (2019)
In recent years, several studies have been developed addressing the subject of individual technology acceptance, and new models have been developed and presented. These models aim to understand and identify the determinants of acceptance of technologies that lead to successful adoption. This dissertation aims to study the antecedents of acceptance and adoption of Continuous Auditing (CA) by internal auditors from the perspective of the Unified Theory of Acceptance and Use of Technology (UTAUT). To achieve the research objectives, a quantitative study was carried out and operationalized through an online questionnaire made available to internal auditors. 103 responses were received from 103 auditors. The results indicate that the internal auditor realizes that he will achieve progress in the performance of audit work when using AC. Additionally, the use of CA systems is facilitated by the positive perceptions of the internal auditors in relation to the expectation of effort. Realize that the other auditors expect him to use CA technology. They show that the lack of organizational infrastructure and technological support negatively affect the decision to use electronic tools. The results also indicate that no matter how competent an internal auditor is, using a system, if the organizations does not have adequate resources, such as technology infrastructure, to support the use of the system; in this case, the behavioral expectation of the internal auditor in the use of this system is reduced. This dissertation presents significant contributions, with impacts to the Boards of Directors, Audit Committees, Senior Management, academics and professionals interested in the subject